NATIONAL IMAGE OF THE WORLD AS AN ETHNOPOETICAL CATEGORY IN RUSSIAN LITERATURE - Sheshunova S. V. (Проблемы исторической поэтики, 2008)
This article explains the usage of the term "national image of the world" in literary studies by analogy with the term "language picture of the world" used in linguistics, as well as specifies a range of components of national image of the world in Russian literature of the 19th—20th centuries. Examples from the novels "In the Forests" and "On the Hills" by Pavel Melnikov-Pechersky, the novel "Nanny from Moscow" by Ivan Shmelyov and especially the novel "The Red Wheel" by Alexander Solzhenitsyn are given to illustrate the key points of this article.